Microwave-Assisted Synthesis of Fused and Substituted 2-Aminopyridines from β-Halo α,β-Unsaturated Aldehydes - Gogoi, Junali; Gogoi, Pranjal; Goswami, Limi; Boruah, Romesh C. (Synthesis, 2015)
2-Aminopyridines were synthesized from β-halo α,β-unsaturated aldehydes by a microwave-assisted Knoevenagel reaction. The β-halo-α,β-unsaturated aldehydes were, in turn, efficiently synthesized from the corresponding ketones by a Vilsmeier formylation reaction. The protocol was used to synthesize several novel steroidal and nonsteroidal fused 2-aminopyridine derivatives.
Keywords: steroids; pyridines; enals; Knoevenagel reactions; cyclizations